2004
DOI: 10.1101/lm.77504
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Recovery

Abstract: Spontaneous recovery from extinction is one of the most basic phenomena of Pavlovian conditioning. Although it can be studied by using a variety of designs, some procedures are better than others for identifying the involvement of underlying learning processes. A wide range of different learning mechanisms has been suggested as being engaged by extinction, most of which have implications for the nature of spontaneous recovery. However, despite the centrality of the notion of spontaneous recovery to the underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
328
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(358 citation statements)
references
References 43 publications
24
328
0
1
Order By: Relevance
“…This can also be seen in cued associations; animals are likely to "spontaneously recover" responding to a cue they have not been exposed to for a long time (Pavlov, 1927;Rescorla, 2004;Robbins, 1990). This cued renewal of responding is thought to underlie cued relapse to addiction (Childress, Ehrman, Rohsenow, Robbins, & O' Brien, 1992;Childress et al, 1993;Childress, McLellan, Ehrman, & O'Brien, 1988;O'Brien, Childress, McLellan, & Ehrman, 1992).…”
Section: Cued Renewalmentioning
confidence: 99%
See 3 more Smart Citations
“…This can also be seen in cued associations; animals are likely to "spontaneously recover" responding to a cue they have not been exposed to for a long time (Pavlov, 1927;Rescorla, 2004;Robbins, 1990). This cued renewal of responding is thought to underlie cued relapse to addiction (Childress, Ehrman, Rohsenow, Robbins, & O' Brien, 1992;Childress et al, 1993;Childress, McLellan, Ehrman, & O'Brien, 1988;O'Brien, Childress, McLellan, & Ehrman, 1992).…”
Section: Cued Renewalmentioning
confidence: 99%
“…Current theories of extinction in both psychology and neuroscience (Bouton, 2002(Bouton, , 2004Bouton et al, 2006;Delameter, 2004;Milad & Quirk, 2002;Myers & Davis, 2002;Quirk et al, 2006;Rescorla, 2004) are based on the addition of new variables, often identified as contextual (Bouton, 2002(Bouton, , 2004Bouton et al, 2006) or inhibitory (Delameter, 2004;Pavlov, 1927). In any content-addressable memory, the cues provide inputs from which a unique state can be recalled.…”
Section: Relation To Other Models Of Extinction and Renewalmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors would be expected to interact with each other such that the precise experimental conditions used by independent laboratories would differentially reveal recovery of the cued fear responses. Although most accounts of extinction and spontaneous recovery suggest that the original learning remains unchanged, there is ultimately a dissipation of the extinction memory at the behavioral level, the mechanisms underlying the loss of the extinction trace or its control over behavioral responses remain to be determined (for review, see Rescorla 2004). The durable extinction we show here may be a consequence of the context entering into primary excitatory and inhibitory associations with the US during conditioning and extinction, respectively.…”
Section: Discussionmentioning
confidence: 83%